2016
DOI: 10.1073/pnas.1618650114
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly expressed LGR4 empowers Wnt signaling in multiple myeloma by hijacking osteoblast-derived R-spondins

Abstract: The unrestrained growth of tumor cells is generally attributed to mutations in essential growth control genes, but tumor cells are also affected by, or even addicted to, signals from the microenvironment. As therapeutic targets, these extrinsic signals may be equally significant as mutated oncogenes. In multiple myeloma (MM), a plasma cell malignancy, most tumors display hallmarks of active Wnt signaling but lack activating Wnt-pathway mutations, suggesting activation by autocrine Wnt ligands and/or paracrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 63 publications
2
42
1
Order By: Relevance
“…It has been reported that LGR4, 5, and 6 are strong potentiators of Wnt/β‐catenin signaling . Several studies have highlighted the crucial role of LGR4 in the promotion of osteoblast differentiation by activating the Wnt signaling pathway . Intriguingly, in the present study, BMP9 had no effect on the expression level of the LGR4 gene but dramatically augmented the expression of the LGR6 gene.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that LGR4, 5, and 6 are strong potentiators of Wnt/β‐catenin signaling . Several studies have highlighted the crucial role of LGR4 in the promotion of osteoblast differentiation by activating the Wnt signaling pathway . Intriguingly, in the present study, BMP9 had no effect on the expression level of the LGR4 gene but dramatically augmented the expression of the LGR6 gene.…”
Section: Discussioncontrasting
confidence: 56%
“…Instead, oncogenic Wnt pathway activity in MM involves autocrine and/or paracrine Wnt ligands 19,21,32,33 and is potentiated by aberrant expression and turnover of Wnt (co)receptors and transcriptional activators, as well as by loss of negative Wnt pathway regulators. These activating events include aberrant expression of the R-spondin receptor LGR4 34 and of the transcriptional coactivator BCL9, 35,36 epigenetic silencing of the feedback inhibitors secreted Fzd-related proteins and DKK1, 21,33 and mutational inactivation of CYLD, a deubiquinating enzyme that negatively regulates Wnt. 37 Given the ligand dependence of Wnt pathway activation in MM, targeting of Wnt receptors and coreceptors, disconnecting the MM cells from their growth-promoting microenvironment, is a potentially promising therapeutic strategy for MM.…”
Section: Introductionmentioning
confidence: 99%
“…The CML-BC cell line KBM5 and the imatinibresistant KBM5-T315I subclone were kind gifts from Dr. Carter and Dr. Andreeff (MD Anderson Cancer Center, Houston, TX). The multiple myeloma (MM) cell lines NCI-H929, ANBL-6, XG-1 and UM-3 used in this study were described earlier [41]. All cell lines were maintained in Iscove's Modified Dulbecco's Medium (IMDM) (Gibco Life Technologies, Bleiswijk, The Netherlands) supplemented with 2 mM L-glutamine, 100 U/ mL penicillin, 100 μg/mL streptomycin and 10% fetal calf serum (FCS).…”
Section: Cell Lines Primary Patient Samplesmentioning
confidence: 99%